Program Air Siap Minum Untuk Siswa dan Penduduk Terdampak Gempa di Sekolah Dasar Nengeri 3 Malaka Teluk Nara Pemenang, Kabupaten Lombok Utara - Made Sutha Yadnya; Ahmad Tahmid; Abdulah Zainuddin; Bulkis Kanata; Teti Zubaidah; Paniran Paniran (Jurnal Gema Ngabdi, 2020)
Since the magnitude 7 magnitude earthquake occurred in August 2018, Lombok Island, especially North Lombok Regency, has been severely affected by infrastructure damage. From the data available, there are very few sources of clean water and are scarce. For this reason, in March 2019 the University of Mataram Community Service Team was represented by PUI Geomagnetic together with the largest water pump company in the world, Xylem Inc. installed a water pump at SDN 3 Teluk Nara Pemenang. The result of pumping water is clean water ready to drink.